Perancangan Sistem Pemilihan Ketua Osis Dan Ketua Kelas Di Smk Yuppentek 2 Kabupaten Tangerang Berbasis Web Menggunakan Unified Modelling Language (Uml) - Prasetyo, Dimas Nur; Rahmawati, Diah; mahmudin, Mahmudin (Universitas Islam Syekh Yusuf, 2023)
High School for the Promotion of Technology Education Foundation (YUPPENTEK Vocational School) 2 Tangerang Regency is a place for gaining knowledge for the future, particularly in terms of organization. Within the school's organizational structure, having a president or representative for its members is essential, and this position is typically filled through voting or elections. The process of electing the Student Council President (OSIS) at the school is still considered to be conventional, involving manual vote counting and paper-based data collection, which poses risks of data loss and waste from unused paper. This research aims to design a web-based system for electing both the OSIS president and class representatives using the Unified Modeling Language (UML), a visual method used for planning, describing, and illustrating various aspects of software systems.The results of the research demonstrate that the system for electing the OSIS president and class representatives can be successfully implemented with the active participation of students and organization members. This system offers advantages in terms of data collection, vote counting, and ease of access for participants.